Response to: Management of traumatic brain injury: practical development of a recent proposal. Issue 4 (2022) - Li, Lucia M; Dilley, Michael D; Carson, Alan; Twelftree, Jaq; Hutchinson, Peter J; Belli, Antonio; Betteridge, Shai; Cooper, Paul N; Griffin, Colette M; Jenkins, Peter O; Liu, Clarence; Sharp, David J; et al.
No abstract available